Jakie skutki niesie za sobą prywatna własność? - Kwaśnicki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
An attempt to answer some fundamental questions related to property are presented, namely: ‘What is property?’, ‘What are the property rights?’, ‘How do we acquire property?’, ‘What is the impact of private ownership on the economic process?’. The conclusions of that short analysis are following: (1) well-functioning private ownership provides security and prevents acts of violence, (2) in spite of common believe, dominance of private property provides the social scattering of the property and hence dissipation of power and ensures widening of free and peaceful exchange (and through that the welfare growth), (3) as history shows, communist and socialist countries, where there private property were highly limited, have experienced a large concentration of power and a lot of violence.
Keywords: własność prywatna; prawa własności; socjalizm; kapitalizm